Primary care consultations and pain medicine prescriptions: a comparison between patients with and without chronic pain after total knee replacement - Pinedo Villanueva, R; Kolovos, S; Maronga, C; Delmestri, A; Howells, N; Judge, A; Gooberman-Hill, R; Wylde, V (BioMed Central, 2022)
Background Approximately 20% of patients experience chronic pain after total knee replacement (TKR). The impact of chronic pain after TKR on primary care services in the UK is currently unknown. The aim of this study was to compare primary care consultations and pain medicine prescriptions between patients with and without chronic pain after TKR.